Human–coastal coupled systems: Ten questions - Dylan E. McNamara; Eli D. Lazarus; Evan B. Goldstein (Cambridge Prisms: Coastal Futures, 2023)
Given the inevitability of sea-level rise, investigating processes of human-altered coastlines at the intermediate timescales of years to decades can sometimes feel like an exercise in futility. Returning to the big picture and long view of feedbacks, emergent dynamics, and wider context, here we offer 10 existential questions for research into human–coastal coupled systems.